2000
DOI: 10.1016/s0886-3350(00)00747-1
|View full text |Cite
|
Sign up to set email alerts
|

Adhesion of fibronectin, vitronectin, laminin, and collagen type IV to intraocular lens materials in pseudophakic human autopsy eyes

Abstract: The greater amount of protein on the hydrophobic soft acrylate (AcrySof(R)) IOLs seems to support an adhesive mechanism for their attachment to the capsular bag. Fibronectin and vitronectin have functional domains to bind them to lens epithelial cells and the collagenous capsule. This kind of attachment could be a true bioactive bond and may be 1 reason the PCO and neodymium:YAG capsulotomy rates are lower in eyes with a soft acrylate IOL.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
38
1
3

Year Published

2004
2004
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 126 publications
(42 citation statements)
references
References 42 publications
0
38
1
3
Order By: Relevance
“…Studies have shown that due to tackiness of acrylate material to posterior capsule the incidence of PCO is less. [1819]…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that due to tackiness of acrylate material to posterior capsule the incidence of PCO is less. [1819]…”
Section: Discussionmentioning
confidence: 99%
“…17 The Ra values of the posterior surface of the Hoya and Nidek IOLs only changed a little, while those of the Alcon IOLs increased. The Alcon Acrylof IOLs had a greater surface roughness, which may increase adhesion of proteins, such as fibronectin, to the optic surface, 18 resulting in an increase in the sticky nature and inducing adhesion of LECs 19 and collage membranes, 20 further leading to the prevention of posterior capsule opacification.…”
Section: Discussionmentioning
confidence: 99%
“…Immunohistochemical study shows that this adhesion is mediated by fibronectin. [1011] Similarly, posterior capsule is also assumed to be adhered to the posterior surface of the IOL and bioadhesive nature of the IOL may act as an additional adhesive force. Residual cortical fibers and capsular ‘E’ cells are trapped initially within a sealed structure created by anterior capsular flap, posterior capsule, and edge of the IOL.…”
Section: Discussionmentioning
confidence: 99%